Recent advances on optimum-path forest for data classification: Supervised, semi-supervised, and unsupervised learning - Papa, João Paulo [UNESP]; Amorim, Willian Paraguassu; Falcão, Alexandre Xavier; Tavares, João Manuel R.S. (World Scientific Publishing, 2015)
Although one can find several pattern recognition techniques out there, there is still room for improvements and new approaches. In this book chapter, we revisited the Optimum-Path Forest (OPF) classifier, which has been evaluated over the last years in a number of applications that consider supervised, semi-supervised and unsupervised learning problems. We also presented a brief compilation of a number of previous works that employed OPF in different research fields, that range from remote sensing image classification to medical data analysis.